Pemanfaatan Plankton sebagai Sumber Makanan Ikan Bandeng di Waduk Ir. H. Juanda, Jawa Barat - Deden Ibnu Aqil; Lily Surayya Eka Putri; Lukman Lukman (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2013)
Introducing of Milkfish (Chanos chanos) was aimed to utilize natural food from plankton that were abundant in Ir. H. Juanda Reservoir, West Java. This research aimed to know plankton utilization by Milkfish in Ir. H. Juanda Reservoir, West Java. The research was conducted from February to July 2010 at 4 stations of sampling which representing the reservoir condition. The fishes collected based on the catch of fishermen. The sample was analyzed in physiology laboratory of Center Research for Limnology. The result of this research showed that the main food were plankton 43%, detritus 46%, and complement food were vegetation 11%. The domination food from the phytoplankton were Bacillariophyceae and zooplankton were Copepoda.